(3GdJehjd GdOhdj (B/s - (3eWQ, ehSi SYjOs; (3TbjQj, fhQj ehSis ((3YeGf(B: s (3OGQ UaGA ddfTQ(B, s, 2008)
(3jMJhj GdcJGH Ydi GdeMGhQ GdJGdjI(B:(3ejRGf GdeOahYGJ,GdYedGJ GdCLfHjI,SYQ GdUQa GdCLfHjI,JSejI CSYGQ GdYedGJ GdCLfHjI, CSYGQ GdYedGJ GdCLfHjI,ChVGY GdeJYGedjf,YedjGJ GdJYGed GdBLd, JMdjd GdNjGQGJ, YedjGJ GdJHOjd Ch GdebGjVI,eQGbHI YedjGJ GdJYGed,GdeDSSGJ GdeGdjI GdOhdjI,GdTQcGJ eJYOOI GdLfSjGJ(B.s
(3HjHdjhZQGajG U(B.192s
Keywords: (3GdGbJUGO GdOhdjs; (3GdYdGbGJ GdfbOjI GdOhdjIs